1998
DOI: 10.5694/j.1326-5377.1998.tb139080.x
|View full text |Cite
|
Sign up to set email alerts
|

An epidemic of renal failure among Australian Aboriginals

Abstract: ObjectiveTo define recent trends (1993‐1996) in incidence of endstage renal disease (ESRD) among Australian Aboriginal people in the Top End of the Northern Territory (NT). DesignAnalysis of hospital and clinical records of the Darwin‐based ESRD treatment program from 1993 to 1996 and comparison with data accumulated since 1978. ParticipantsAll people entering the ESRD treatment program from 1978 to 1996. Main outcome measuresNumber of patients treated for ESRD; their ethnicity, age and sex; comorbidities in A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
79
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(84 citation statements)
references
References 7 publications
5
79
0
Order By: Relevance
“…In the United States, the age-adjusted death rate for diabetes mellitus in American Indians/Alaskan Natives in 2006 was 1.9 times higher than in US non-Hispanic whites (39.6 and 20.4 per 100,000, respectively) (US Department of Health and Human Services, 2006). The severity of certain diabetic complications including endstage renal disease and lower-extremity amputation tends to be significantly higher among Indigenous groups (Chaturvedi et al, 2001;Naqshbandi et al, 2008;Spencer et al, 1998). Addressing Type 2 diabetes and the background risk factors (including obesity, sedentary behavior, and gestational diabetes) is critical to reducing Indigenous health inequalities in these countries.…”
Section: Introductionmentioning
confidence: 99%
“…In the United States, the age-adjusted death rate for diabetes mellitus in American Indians/Alaskan Natives in 2006 was 1.9 times higher than in US non-Hispanic whites (39.6 and 20.4 per 100,000, respectively) (US Department of Health and Human Services, 2006). The severity of certain diabetic complications including endstage renal disease and lower-extremity amputation tends to be significantly higher among Indigenous groups (Chaturvedi et al, 2001;Naqshbandi et al, 2008;Spencer et al, 1998). Addressing Type 2 diabetes and the background risk factors (including obesity, sedentary behavior, and gestational diabetes) is critical to reducing Indigenous health inequalities in these countries.…”
Section: Introductionmentioning
confidence: 99%
“…Rates of end-stage renal disease are also extremely high, particularly among those living in the Northern Territory and other remote areas [2]. In one Aboriginal community, albuminuria has been shown to be predictive of subsequent end-stage renal disease [3] and death [4].…”
Section: Introductionmentioning
confidence: 99%
“…In these communities, chronic renal disease and end-stage renal failure also occur in adults at alarming rates. 6,7 PSGN is usually followed by clinical recovery over several days to weeks, and the long-term outlook has generally been regarded as excellent, with no increase in risk of urinary abnormalities or hypertension. [8][9][10] However, some studies have suggested that there is an increase in chronic renal impairment after this illness.…”
mentioning
confidence: 99%